2002
DOI: 10.1177/026119290203002s24
|View full text |Cite
|
Sign up to set email alerts
|

Information: Needs for the Future

Abstract: The four central questions surrounding the use of information are: where to find it; how to find it; how to present it; and how to maintain information availability and information literacy. It is usually assumed that the main source of information for most scientists is the peer-reviewed journal literature. Traditional journal publishing is beset with a number of problems. Although electronic publishing might possibly solve some of these, it in turn introduces new problems. Further problems arise with respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…To facilitate the retrieval of information regarding the possibilities for implementing the 3Rs in a specific research field/study, a lot of effort has been put into the development of specific 3R databases 2,3 and of guidelines on how to search for 3R information. 4–7 An earlier survey by Leenaars et al. revealed that, despite all these developments, there is still much room for improvement in the way scientists currently retrieve information about the 3Rs (from databases).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…To facilitate the retrieval of information regarding the possibilities for implementing the 3Rs in a specific research field/study, a lot of effort has been put into the development of specific 3R databases 2,3 and of guidelines on how to search for 3R information. 4–7 An earlier survey by Leenaars et al. revealed that, despite all these developments, there is still much room for improvement in the way scientists currently retrieve information about the 3Rs (from databases).…”
mentioning
confidence: 99%
“…To facilitate the retrieval of information regarding the possibilities for implementing the 3Rs in a specific research field/study, a lot of effort has been put into the development of specific 3R databases 2,3 and of guidelines on how to search for 3R information. [4][5][6][7] An earlier survey by Leenaars et al revealed that, despite all these developments, there is still much room for improvement in the way scientists currently retrieve information about the 3Rs (from databases). 8 From this survey, it was concluded that searching for the 3Rs is not considered to be an integral part of the research process (and thus is not funded), knowledge of 3R databases is minimal, and search skills in general are limited.…”
mentioning
confidence: 99%
“…The most frequently used databases, PubMed (Medline) and ISI Web of Science, are not very well indexed for conducting Three Rs searches (8). PubMed has a Medical Subject Headings (MeSH) thesaurus term 'Animal Use Alternatives', which results in only about 1700 hits from the multimillion record database, and is therefore quite useless.…”
Section: Discussionmentioning
confidence: 99%
“…Most scientists receive, as part of their education, basic training in how to search in bibliographical databases such as PubMed (Medline) and ISI Web of Science. These databases are not particularly well equipped for conducting Three Rs searches (8). Furthermore, Three Rs information is spread widely over a large number of databases and websites (9).…”
Section: Introductionmentioning
confidence: 99%
“…The members of the SG also suggested that a database for alternative methods (applying to all the Three Rs) should be established at the European level. However, several very useful databases and sources of information on alternatives already exist (67)(68)(69)(70)(71). For example, the following databases are useful starting points for accessing the literature on alternatives.…”
Section: The View Of the Sgmentioning
confidence: 99%